PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERBANKAN - Dwi Wantoro (AKT 15 UMY 127, 2015)
*127 The study aimed to analyze the influence of Good Corporate Governance’s mechanism that consist of institutional ownership, managerial ownership, board of commissioners, board of independent, board of directors, audit committee, and firm size through the banking performance which listed in Indonesian stock Exchanges in the period of 2010-2013. Total samples that used in this study are 37 banks. The testing of hypothesis in this study uses descriptive analysis, classical assumptions, regression analysis with α 0,05, t test, and coefficient of determination. The result of this study showed a significance influence through the banking performance meanwhile the institutional ownership, managerial ownership, board of commissioners, board of independent, board of directors, audit committee didn't show the significance effect to the banking performance.